Differences in the management of heart failure with preserved ejection fraction among physicians from Europe, the Middle East and North Africa: an international survey - Omar Ahmad; Nathan Mewton; Dania Mohty; Najmeddine Echahidi; Clara Saldarriaga; Anastasia Shchendrygina; Sydney Goldfeder de Gracia; Mohamed H Omer; Mosaad Alhussain; Suleiman M Kharabsheh; Fakhr Ayoubi; Kamal Alghalayni; et al. (Open Heart)
Background Heart failure with preserved ejection fraction (HFpEF) poses global diagnostic and therapeutic challenges, with potential regional differences in clinical practice that remain underexplored. This study aimed to map physician-reported HFpEF diagnostic and management practices across Europe and the Middle East-North Africa (MENA) region to identify similarities, differences and opportunities for improved care.Methods An independent, academically developed survey consisting of 29 questions was designed through expert collaboration to capture detailed information on physician demographics, diagnostic strategies, screening practices, pathophysiological understanding and treatment approaches for HFpEF. The survey was validated by heart failure specialists to ensure relevance and accuracy and distributed widely through professional societies, email and social media channels to reach cardiologists, general practitioners and other physicians involved in heart failure care across Europe and MENA.Results A total of 723 physicians participated (77 from MENA, 646 from Europe). The proportion of heart failure specialists was higher in Europe (26%) than in MENA (12%, p<0.001), while general cardiologists comprised a larger share in MENA (81% vs 59%, p<0.001). Natriuretic peptide testing use was lower in MENA (82%) compared with Europe (92%, p=0.023). Pharmacotherapy preferences showed both regional similarities and differences, with SGLT2 inhibitors being the most preferred drug of choice universally. In contrast, there was a higher ranking of mineralocorticoid receptor antagonists in Europe (p=0.007) and greater reported use of angiotensin receptor-neprilysin inhibitors in MENA (p=0.03).Conclusion This large international survey offers a descriptive mapping of HFpEF care practices across Europe and MENA, revealing overall guideline alignment but also regional differences in diagnostic test use and pharmacotherapy preferences. These findings underscore the need for targeted education, improved diagnostic and therapeutic access and tailored guideline implementation to ensure equitable, evidence-based HFpEF management across diverse healthcare settings.